Design of Augmented Reality as a Promotional Media at University of Raharja - Saryani Saryani; Novi Cholisoh; Gian Nurwana (International Institute for Advanced Science & Technology (IIAST), 2022)
Augmented Reality is a technology that combines two-dimensional and or three-dimensional virtual objects into a natural three-dimensional environment and then projects these virtual objects in real-time. Multimedia technology has increasingly been applied in various industrial sectors as an information media for various purposes and is no exception as a promotional media. The University of Raharja, as an example of an ICT college in Tangerang, is currently experiencing very rapid development. School of Management and Computer Information Raharja evidenced it into the University of Raharja. This is, of course, a very positive impact, especially for the promotion activities of the University of Raharja. In this study, an Augmented Reality design for the University of Raharja was made to be used as promotional media.